Yuting Shen; Yanzhen Zhu; Rui Yang ; Towards Cultural Self-awareness in Research: A Study of Chinese Scholars in the Humanities and Social Sciences - Yuting Shen; Yanzhen Zhu (Corresponding Author) (Higher Education, 2025)
The global knowledge asymmetries are increasingly interrogated by non-Western humanities and social sciences (HSS) scholars whose research is anchored in local contexts yet must adhere to international (Western) standards. Under this circumstance, the study aims to examine how the cultural self-awareness of non-Western HSS scholars is manifested in research through a Chinese lens. Based on previous theoretical perspectives and Fei Xiaotong’s theory of cultural self-awareness, the study first constructs two analytical dimensions: academic self-reflexivity and cultural appreciation attitudes. It then performs a qualitative investigation including 28 Mainland Chinese HSS scholars through interviews and literature analyses. The findings highlight key principles for academic self-reflexivity, namely reflecting on intellectual extraversion, dichotomous thinking, and the reemphasis on Chinese culture and knowledge. The cultural appreciation attitudes are also elaborated, which are embodied in the recognition and revaluation of traditional Chinese knowledge, the continued appreciation of modern Western knowledge, and the synthesis of different cultures and knowledge in research. These findings develop Fei’s cultural self-awareness theory and add new discourses to address global knowledge imbalances, promoting a more diverse and inclusive global higher education landscape.